Winter water variability in the Indian Ocean sector of Southern Ocean during austral summer. (August 2020) - Sabu, P.; Libera, Stephy Ann; Chacko, Racheal; Anilkumar, N.; Subeesh, M.P.; Thomas, Antony P.
Abstract: Winter Water (WW) is a feature in the upper layers of the Southern Ocean during austral summer. The interaction of this cold water with surface and deeper subsurface layers can alter the heat budget as well as the carbon cycle. However, the structure and characteristics of the WW in the Southern Ocean is poorly understood due to the lack of in-situ data. In this study, hydrographic data collected from the Indian expeditions during 2010 and 2011 and from other expeditions during 2003, 2006 and 2007 in the Southern Ocean have been utilized to understand the WW variability and its characteristics in the region between 40°E and 90°E. The analysis shows large zonal variations in the distribution of WW during austral summer. East of 60°E, the WW shows warmer temperature with weaker gradients than the western side, which is observed to have a larger meridional extension. The high frequency of eddies, surface warming and upwelling of the Upper Circumpolar Deep Water due to shallow bathymetric features of the Kerguelen Plateau situated in the eastern side of the study region is proposed as the major mechanisms for this variability. The direct impact of Southern Annular Mode on WW variability is investigated and a short term response is observed.